A glutathione-depleting chemodynamic therapy agent with photothermal and photoacoustic properties for tumor theranostics. Issue 3 (8th January 2020) - Liu, Feng; Lin, Lin; Sheng, Shu; Xu, Caina; Wang, Yanbing; Zhang, Ying; Wang, Dianwei; Wu, Jiayan; Li, Yanhui; Tian, Huayu; Chen, Xuesi
Abstract : A glutathione-depleting multifunctional chemodynamic therapy agent for tumor theranostics. Abstract : Nowadays, Fenton reaction-based chemodynamic therapy (CDT) strategies have drawn extensive attention as tumor-specific nanomedicine-based therapy. Nevertheless, current existing CDTs normally suffer from therapeutic bottlenecks such as the scavenging of hydroxyl radical (˙OH) by intracellular antioxidants and unideal therapeutic outcome of single treatment modality. Herein, we constructed novel all-in-one AFP nanoparticles (NPs) as CDT agents through a one-pot process for multifunctional nanotheranostics. The as-constructed AFP NPs could simultaneously produce ˙OH through the Fenton reaction and scavenge intracellular glutathione, functioning as self-reinforced CDT agents to achieve tumor-triggered enhanced CDT (ECDT). In addition, the AFP NPs possessed the capability of H2 O2 and acid-boosted photoacoustic imaging and photothermal therapy, enabling a precise and effective tumor therapeutic outcome with minimal nonspecific damage in combination with ECDT. Our novel nanoplatform would open new perspectives on multi-functional CDT agents for accurate and non-invasive tumor theranostics.